2019 IEEE Symposium on Security and Privacy (SP) 2019
DOI: 10.1109/sp.2019.00021
|View full text |Cite
|
Sign up to set email alerts
|

SoK: The Challenges, Pitfalls, and Perils of Using Hardware Performance Counters for Security

Abstract: Hardware Performance Counters (HPCs) have been available in processors for more than a decade. These counters can be used to monitor and measure events that occur at the CPU level. Modern processors provide hundreds of hardware events that can be monitored, and with each new processor architecture more are added. Yet, there has been little in the way of systematic studies on how performance counters can best be utilized to accurately monitor events in real-world settings. Especially when it comes to the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 79 publications
1
67
0
Order By: Relevance
“…Instead, when using IF with performance metrics (+ coarse-grain power statistics) we observed a high F1-score, with 0 % of FA rate, in the system in idle, HPCG, and QE, while we obtained a poor F1-score for Gromacs and HPL, and a really low F1-score with high FA rate for NPB btC9, and NPB btC16. When looking at the overall F1-score, we obtain a low value of 0.758, which is in line with results in [34], [35], when using tree-based models with performance counters for malware detection (reason why they do not advice this technique for security purposes). Finally, in the case of AE, we obtain poor scores for all benchmarks, except for HPCG, NPB btC9, and NPB btC16, and an overall F1-score of 0.627.…”
Section: B Malware Detection Resultssupporting
confidence: 86%
“…Instead, when using IF with performance metrics (+ coarse-grain power statistics) we observed a high F1-score, with 0 % of FA rate, in the system in idle, HPCG, and QE, while we obtained a poor F1-score for Gromacs and HPL, and a really low F1-score with high FA rate for NPB btC9, and NPB btC16. When looking at the overall F1-score, we obtain a low value of 0.758, which is in line with results in [34], [35], when using tree-based models with performance counters for malware detection (reason why they do not advice this technique for security purposes). Finally, in the case of AE, we obtain poor scores for all benchmarks, except for HPCG, NPB btC9, and NPB btC16, and an overall F1-score of 0.627.…”
Section: B Malware Detection Resultssupporting
confidence: 86%
“…The two comparison papers mentioned above [88,90] point out the weak connection between HPC measurements and the high-level code executed by malware, but the same conclusion can be drawn by side-channel analysis using external hardware. The conclusion is that side-channel analysis is only as strong as the statistical correlation between two separate views: high-level code and low-level hardware.…”
Section: Side-channel Analysismentioning
confidence: 80%
“…Using HPCs to detect malware has been tested by various researchers with inconclusive results. One study [88] showed that while it is possible to use HPCs to detect ROP (return-oriented programming) execution, HPCs are less effective for malware detection. ROP is a common technique used by malware to counter anti-exploit mechanisms, which is based on reusing compiled code that was previously loaded into the victim's RAM.…”
Section: Side-channel Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this technology is used to establish the so-called mobile ad-hoc clouds, which take advantage of unused resources of nearby devices to provide cloud services, such as data and computation offloading. This is also a typical case of IoT environment, where IoT devices communicate with each other on short-distance channels [10].…”
Section: Introductionmentioning
confidence: 99%